1983
DOI: 10.1902/jop.1983.54.6.325
|View full text |Cite
|
Sign up to set email alerts
|

Healing Responses of Human Intraosseous Lesions Following the Use of Debridement, Grafting and Citric Acid Root Treatment: II. Clinical and Histologic Observations: One Year Postsurgery

Abstract: This report details histologic healing responses at intrabony sites within two patients about 1 year after surgery. Treatment consisted of open flat debridement of the lesions. At specific sites, augmenting procedures such as autogenous grafts, allografts, synthetic grafts and citric acid root treatment were utilized. In addition, notches were made through calculus prior to root planing at specific root surfaces. These notches were placed at varying distances from the base of the lesion. Patients were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
1
4

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 32 publications
1
49
1
4
Order By: Relevance
“…Regarding bone replacement grafts, from a biologic point of view, autogenous bone grafts have been considered the gold-standard material with the most predictable outcomes [3,4], but they require a second surgical site to harvest the graft from a donor area. Alternatively, xenografts and allografts have been well documented to be suitable as bone replacement grafts [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding bone replacement grafts, from a biologic point of view, autogenous bone grafts have been considered the gold-standard material with the most predictable outcomes [3,4], but they require a second surgical site to harvest the graft from a donor area. Alternatively, xenografts and allografts have been well documented to be suitable as bone replacement grafts [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…2 This histological evidence is supported by clinical results that include bone fill of osseous defects and gain of clinical attachment levels. Currently, several materials have met these criteria in the human model: intraoral autogenous bone, [3][4][5] demineralized freeze-dried bone allograft (DFDBA), 6,7 DFDBA with bone morphogenetic protein (BMP), 8 barrier membranes, [9][10][11][12] citric acid application, 13 bovine-derived xenograft (BDX), 14,15 and enamel matrix derivative (EMD). 16,17 EMD and BDX have recently been introduced as part of the armamentarium for regenerative therapy.…”
mentioning
confidence: 99%
“…Caffesse et al,64 using a dog model, and Caton et al65 in a primate model have shown that the bulk of these changes are complete within 3 to 5 months postsurgery. Human histological studies of periodontal regeneration are scarce; however, Stahl et al6667 have shown significant tissue regeneration at both 6-and 12-months postsurgery. Unfortunately, no attempt was made to quantitate and compare healing berevealed a mean defect resolution of 4.72 mm, which was the combination of 4.39 mm bone fill and 0.33 mm of crestal…”
mentioning
confidence: 99%